2011
DOI: 10.1016/j.jhazmat.2010.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Use of electrochemical techniques to characterize methamidophos and humic acid specifically adsorbed onto Pt and PtO films

Abstract: Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were employed to study methamidophos (MAP) and humic acid (HM) specifically adsorbed onto Pt and PtO films in pH-7.0 universal buffer. The approach was found to be sufficiently selective for use in studies involving adsorption of species in environmental systems (e.g., soil minerals), typically evaluated by batch experiments and high performance liquid chromatography (HPLC) or gas chromatography (GC). The proposed method allowed quantific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Observation showed that HA removal at alkaline condition is not noticeable, however, at neutral and acidic pH, the HA removal was obvious. These findings were confirmed by other researchers . Considering the HA precipitation in acidic solution (pH <2) , the range 3–8 for pH was selected for the experiments.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Observation showed that HA removal at alkaline condition is not noticeable, however, at neutral and acidic pH, the HA removal was obvious. These findings were confirmed by other researchers . Considering the HA precipitation in acidic solution (pH <2) , the range 3–8 for pH was selected for the experiments.…”
Section: Resultssupporting
confidence: 78%
“…They explained that small electrode interval, high current density, and lower pH value leads to higher removal rate of HA. Adsorption of HA on Pt and PtO films at neutral pH was investigated with the cyclic voltammetry (CV) and electrochemical impedance spectroscopy by Silva et al . Alsheyab and Muñoz used H 2 O 2 /O 3 , O 3 /UV and H 2 O 2 /O 3 /UV methods with 0.04 H 2 O 2 /O 3 at 20 min to remove synthetic humic solution; where 78% and 50% of TOC and COD, respectively, were removed and the best result was achieved with H 2 O 2 /O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the width of the double-layer-charging zone is larger in the Mef p-1 solution, indicating that the adsorbed protein is subjected to an electrochemical oxidation/reduction in this region. 42 Pt oxidation and reduction processes occur in region III. The oxidation of Pt in acidic solutions involves the following two steps: the discharge of H 2 O, forming chemisorbed oxygen (eq 3), and interfacial place exchange, forming a quasi-3D lattice comprising Pt 2+ and O 2− (eq 4).…”
Section: Resultsmentioning
confidence: 98%
“…Despite the existence of an electrostatic repulsion between the sample and Mefp-1 molecules, the difference in curves a and b (Figure ) suggests the presence of the protein on the Pt surface. Moreover, the width of the double-layer-charging zone is larger in the Mefp-1 solution, indicating that the adsorbed protein is subjected to an electrochemical oxidation/reduction in this region …”
Section: Resultsmentioning
confidence: 99%